The complete plastid genome and phylogenetic analysis of Gracilaria textorii - Weizhou Chen; Tao Liu; Xianming Tang; Xuli Jia; Xiangyu Wu (Mitochondrial DNA. Part B. Resources, 2019)
The complete plastid genome of Gracilaria textorii, a marine red macroalga, was determined and analyzed. The plastid genome sequence of G. textorii is 179,609 bp. It contains 237 genes, including 203 protein-encoding genes, 30 tRNA genes, 3 rRNA genes, 1 ribonuclease gene, and 1 intron inserted into the trnM gene. Phylogenetic analysis showed that G. textorii clustered together with Gracilaria salicornia, which helps the better understanding of Gracilaria evolution process.